Evaluation on the application of conjugate materials in the sound effect and stage effect of modern dance - Jia, Di (Frontiers in Chemistry, 2023)
The emergence and application of conjugate materials provide a broader space for the performance of sound and presentation effects on the modern music stage. This article compared and analyzed the application of conjugated materials and traditional methods in modern dance sound effects and stage presentation effects through experiments, found that the application of conjugated materials on modern stages had the effect of enhancing visual effects. Its overall reflectivity, color saturation, brightness, transparency, etc. remain in the range of 78%–97%, which is better than traditional methods. In addition, the use of conjugated materials can also improve auditory performance, have greater penetration and durability, and reduce the impact of external noise; in terms of audience experience and dancer experience, the average proportions also reached 87.8893% and 89.3867% respectively. In addition, it also has high temperature resistance and antibacterial effects, with a maximum temperature resistance value of 314.28°C and an antibacterial effect of 95.86%, indicating that it can still maintain stability under high temperature conditions and has a good inhibitory effect on the proliferation of bacteria and viruses. These findings will lay the foundation for further expanding the application of conjugated materials on the modern dance stage.